Preconception Stunting Prevention Education in Premarital Classes on the Knowledge and Attitudes of Prospective Brides Lady Wizia1, Suci Rahmadheny2, Laura Dwi Putri 3 - Wizia, Lady; Ramadheny, Suci; Dwi Pratiwi, Laura (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Background: The stunting rate in Indonesia in 2022 was 21.6%. I was reduced when compared to the SSGI data in 2021 of 24.4%. Stunting prevention is a much more effective step than stunting treatment itself. Prevention of stunting can be done by optimizing the role of mothers in the golden phase of child development. Stunting can be prevented by implementing infant and child feeding, which consists of Early Initiation of Breastfeeding (IMD), exclusive breastfeeding, and timely initiation of complementary feeding. Unfortunately, the achievement of this component of infant and child feeding practices is still far from the target. In 2022, the percentage of infants who received exclusive breastfeeding was 69.7%. Purpose: To determine the influence of Infant Young Child Feeding education on the knowledge and attitudes of pregnant women in the practice of proper feeding of children as a prevention of stunting. Methods:The research method was quasi-experimental design, This study took place in the Kapau and IV Koto Health. The population and sample of the study were pregnant women. 57 pregnant women became samples of this study who taken using consecutive sampling. The intervention in this study was health education of Infant and Young Child Feeding material developed from a module issued by WHO, namely: Infant and Young Child Feeding Counseling: An Integrated Course. Measurement of knowledge and attitudes was carried out before and after the intervention using a questionnaire. Results: The results showed that knowledge and attitudes before and after the intervention obtained a ρ Value of 0.00 (<0.05), so it can be concluded that there is a significant difference in knowledge anda attitude between before and after the intervention. Conclusion: This study found that there was significant difference in knowledge anda attitude between before and after the intervention. it is recommended that health workers can optimize the prevention of stunting using health education.